MULTIMACHINE POWER SYSTEM STABILITY ENHANCEMENT BY USING STATIC SYNCHRONOUS SERIES COMPENSATOR (SSSC) WITH PI CONTROLLER - JOAIB A SHAMALIK,; PROF. Y. D. SHAHAKAR, (International Journal of Innovations in Engineering Research and Technology, 2021)
In recent years power electronics devices has seen many advances, due to this advancement in FACTS devices have increased. Now a days FACTs devices are more efficient and more widely used. Facts devices connected in power system offers many advantages which can solve problems of power system control. FACTs devices can help in improving problems like voltage regulation, transfer capacity enhancement and better power flow control. The main purpose of implementing FACTS devices is to increase transmission line capacity of transmission line. There are two different techniques by which FACTS devices can be made one is by using conventional thyristor, tap changing transformer, reactors and switch capacitors. Whereas second generation uses Gate Turn-Off (GTO) thyristor-switched converters as Voltage Source Converters (VSCs). By using first generation various devices are made viz. SVC, TCSC and TCPS. Second generation has developed few techniques like UPFC, IPFC and SSSC.